One pot synthesis of environmentally friendly lignin nanoparticles with compressed liquid carbon dioxide as an antisolvent. Issue 7 (3rd December 2015) - Myint, Aye Aye; Lee, Hun Wook; Seo, Bumjoon; Son, Won-Su; Yoon, Junho; Yoon, Tae Jun; Park, Hee Jeong; Yu, Jihyun; Yoon, Jeyong; Lee, Youn-Woo
Abstract : Lignin nanoparticles of uniform, small quasi-spherical shape with a relatively high BET surface area (nearly 92 m 2 g −1 ) were synthesized using a facile, one pot technology of a compressed CO2 antisolvent. Abstract : Nanoparticles from commercial kraft lignin were developed using a facile, one pot green technology of a compressed CO2 antisolvent. N, N -Dimethylformamide (DMF) was employed as an organic solvent to prepare the lignin solution. The effects of various process parameters: temperature, pressure, solution flow rate and initial solution concentration, on the product yields, morphology, size, size distribution, surface area and textural properties of the particles were investigated by FESEM, HRTEM analyses and BET analyzers, and their formation mechanisms were deduced by the solubility behavior of lignin with liquid CO2 and DMF in the operating system. Moreover, the quality of lignin nanoparticles were elucidated by ATR-FTIR, XPS, XRD, DSC, TG/DTA and UV-vis measurements. This study showed that as the temperature and lignin concentration increased, and the pressure and solution flow rate decreased, the degree of particle aggregation/coalescence and the size increased along with the broader size distribution. In particular, the coalescence of particles was strongly influenced by the operational pressure, and even more significant with the increasing temperature. As a result, uniform, quasi-spherical nanoparticles with a mean particle diameter of 38 nm were obtained at 280.2 K, 15.0 MPa, and 0.06 kg h −1 of the solution flow rate and 5.3 wt% of the initial lignin concentration. Besides, the lignin nanoparticles have a relatively high BET surface area (nearly 92 m 2 g −1 ) which primarily consisted of mesopores, and exhibited higher UV absorbing and dispersion stability, enhanced solubility, and homogeneous thermal degradation activity as compared with the raw lignin. Noteworthily, their biodegradable and biocompatible character may render them a candidate for applications in cosmetics, health and drug delivery systems.